In vitro gas production and its relationship to in situ disappearance and chemical composition of some Mediterranean browse species (Animal Feed Science and Technology, 2005)
In vitro gas production of seven species (i.e., Arbutus unedo, Calycotum villosa, Erica arborea, Phillyrea angustifolia, Pistacia lentiscus, Myrtus communis, Quercus suber) that are widely browsed by goats were measured through 120 h and related to in situ dry matter disappearance (DMD) and chemical composition. Three goats fitted with ruminal cannulae were used for the in vitro and in situ studies. Browses varied in their crude protein (CP: 55–221 g/kg DM) and neutral detergent fibre (360–551 g/kg DM) contents. High levels of total condensed tannins (TCT) were observed in Pistacia lentiscus, and the lowest levels were in Calycotum villosa and Phillyrea angustifolia. The browses varied widely in potential (145.7–224.0 ml/g DM) and fractional rates (0.038–0.075/h) of gas production, and there were differences among species in DMD (P < 0.05). Gas production at 24 h was positively correlated (P < 0.05) with in situ DM disappearance and CP content, but negatively correlated (P < 0.05) to acid detergent lignin (ADL), free condensed tannins (FCT) and TCT contents. The fractional rate of fermentation (μ) was negatively related (P < 0.05) to FCT (r = −0.81) and TCT (r = −0.83), whereas DMD was only related to acid detergent fibre and ADL content. Results support combined use of gas production and in situ techniques to determine the nutritive value of feeds containing phenolic compounds.